A Comparative Study of Leader Emergence and Engagement in Historic Mission and Charismatic Churches in Ghana - Semeko, A. K. (University of Ghana, 2015)
This study sought to compare leadership emergence and engagement among leaders of charismatic and historic mission churches in Ghana. A combination of qualitative and quantitative approaches were used for the study. The qualitative technique was used to explore the differences in leadership emergence among the leaders of charismatic and historic mission churches. On the other hand, quantitative technique was used to assess the differences in leadership engagement. In all, four hundred and eight church members from the four churches sampled for the study (International Central Gospel Church, Action Chapel International, Methodist Church and Catholic Church) assessed the leadership engagement of their church leaders using a standardized questionnaire. Twenty leaders from four churches were interviewed to find out how they emerged as leaders of their respective churches. The findings showed that, differences in leadership emergence existed among the leaders of charismatic and historic mission churches when they were assessed based on the six phases of leadership emergence by Clinton (1998). One most significant difference with regard to leadership emergence was that, leaders from the historic mission churches emerged as leaders through election while leaders from charismatic churches emerged through appointment. On the other hand, with regards to leadership engagement, it was found that, leaders from the charismatic churches were more engaged than leaders from the historic mission churches. The study therefore recommended that, there is the need for both charismatic and historic mission churches to organize joint leadership training programs which are geared towards adequate training for their church leaders especially on their engagement in their work. The study also recommended that, historic mission churches should emulate the culture of socialization as depicted by the charismatic churches and also develop stronger leadership mentoring programs to equip upcoming and emerging leaders towards excellent performance in their various functions in the church.
Thesis (MPhil.) - University of Ghana, 2015
Keywords: Mission Churches; Leadership Engagement; Church Leadership